PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KOTA MANADO - Alfons Rocky Wengke (COCOS, 2012)
Problems in this research is how the role of agricultural sector through contribution of different sub-sub sector of agriculture to GDP in the period 2000-2010 Manado City, the economics base multiplier of how much production and agriculture sector employment Manado City and North Sulawesi Provinces. The objective to learn the role of the agricultural sector through contribution of agriculture sector to the economy, calculate and learn the economy base multiplier in the agriculture sector period 2000-2010 and to give information to the relevant parties in the context of policy decisions related with regional economic growth. The method uses secondary data obtained from the Central Statistics (BPS) of North Sulawesi and Central Bureau of Statistics Manado and other related agencies. Analysis of the data used in of the research is Contribution Method, Location Quotient (LQ), Economic Base Multiplier. The results showed that the contribution of agriculture to the GDP formation of small relaife Manado City in 2000 until 2006 is relatively small only in the range of 2% per year, whereas in the year 2007 to 2010 decreased in the range  of 1% per year, or with an average contribution of agriculture sector to Manado GDRB per year is only 2,05% of total GDRB Manado. The sector that contributed the most high is the trade sector, restaurants and hotels with an average of 23,33% per year. Electricity, gas and water supply is the smallest sector contributing less than 1% per year or average of 0,70% per year. Construction of the City of Manado GDRB showed a relatively small contribution of the agricultural sector compared with other sectors, but gidue to the importance of the agricultural sector as the main support in the availability of food, it’s progress should be observed in order to either maintain or improve in line with the development of other sector proportionally. Besides agriculture sector also can be used as a buffer in the availability of jobs.